EDUPRANEURSHIP IN FOSTERING ENTREPRENEURIAL VALUES IN EARLY CHILDHOOD - Zayyana Zahrotul Fitri; Nurhusna Kamil; Nurhusni Kamil; Hellya Rahmatun Nisa; Erni Munastiwi (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2023)
In the field of edupreneurship education is a new innovation that is able to produce human resources of superior quality, creative, independent, competitive, and positively contributes to the development of human resources, quality, creative, independent, competitive, and positively contributes for many individuals. This study endeavors to determine edupreneurship in fostering entrepreneurial values in children through guidance and direction from teachers and parents. The research design employed is study literature review. Literature search through google scholar by collecting books and articles related to the keywords "edupreneurship" and "PAUD". The data obtained was filtered by only taking articles related to eduprenuership, entrepreneurial values, and early childhood. Data is processed through a thorough analysis by citing references for information and answering research objectives. Analysis of the research results shows 1) Edupreneurship in fostering entrepreneurial values in children should be through concrete play activities including gardening, market day, cooking class, mini bussines class, traditional games, and mini society 2) Edupreneurship in fostering entrepreneurial values in children must be guided by teachers and parents with steps of plan development, implementation, review of activities, and do follow-up. The research findings contribute to teachers and parents in the form of insights and recommendations that various play activities can foster children's entrepreneurial values that are independent, creative, confident, unyielding, honest, patient, and other entrepreneurial characters.